The Demand for Credit Union Shares - Koot, Ronald S. (Journal of Financial and Quantitative Analysis, 1976)
In this paper, a short-run partial-adjustment model of the demand for credit union shares was specified and estimated with time series data. The estimated results were used to derive long-run, equilibrium demand coefficients and elasticities. The main conclusions are that credit union shares are substitutes for deposits at savings and loan associations, time and savings deposits at commercial banks, and marketable bonds. Moreover, the implications of the statistical results are that credit union and savings and loan shares are more closely related to more liquid assets than to long-term assets. While real income was employed as a constraint variable, it was employed as a maintained hypothesis since the use of a wealth constraint led to perverse results. Also, some evidence was presented that the elasticities of the demand function for credit union shares are different from those of an aggregate savings deposits function. Thus, it is likely that an aggregate demand function will contain aggregation bias.